Do homicide rates increase during weekends and national holidays?. Issue 3 (4th May 2019) - Baird, Alison; While, David; Flynn, Sandra; Ibrahim, Saied; Kapur, Navneet; Appleby, Louis; Shaw, Jenny
ABSTRACT: In the UK there has been limited research examining temporal patterns of homicide. To our knowledge, no studies have linked patterns of homicide to the mental health characteristics of the perpetrator. The study examined a national consecutive case series of homicide offences committed between January 1996 and December 2015 in England. Clinical data were collected by the National Confidential Inquiry into Suicide and Safety in Mental Health (NCISH). During this period 10, 563 people committed a homicide. The offences were more likely to occur at the weekend, mostly on a Saturday. Weekend homicides were associated with: perpetrators under the age of 25, males and alcohol consumption. Homicides increased markedly on New Year's Day, and public holidays. Those with a history of mental illness more commonly committed homicide during weekdays, suggesting a different pattern of offending. No change in pattern was found after licensing hours were extended in 2005 to allow 24-h licencing for the sale of alcohol. A public health approach should focus on educating young people on the health risks associated with alcohol, promoting responsible drinking and conflict avoidance, specifically on special events and at weekends.